Vulnerable Carotid Artery Plaques in Asymptomatic Patients—A Narrative Review - Rehman, Zia Ur (The Arab Journal of Interventional Radiology, 2022)
Over the last two decades, medical management of carotid artery patients has improved significantly. Most patients remain stable on best medical therapy (BMT), making interventions unnecessary in all patients. “Selective” intervention is advocated for only those few patients who are having vulnerable or unstable carotid artery plaques. Literature search was done to explore current concept and role of available investigations to identify vulnerable carotid plaques. Vulnerable plaque is defined as those plaques having active inflammation, high large necrotic lipid content, neovascularity, thin capsule, surface irregularity, or intraplaque hemorrhage. Ultrasound (US) is the simple, noninvasive, cost-effective investigation to differentiate soft (echolucent) from fibrocalcified (echogenic) plaques. It can also comment on other high-risk plaque features such as plaque volume and area. Contrast-enhanced US can visualize neovascularization and plaque surface irregularities better than conventional US. Computed tomography is limited in identifying most high-risk plaque features and is not useful. High-resolution magnetic resonance imaging is the most accurate and externally validated investigation to characterize most high-risk plaque components. Positron emission tomography has emerged as the most promising dynamic investigation to identify and quantify inflammatory plaques and will be clinically very useful in decision making.
Keywords: carotid; asymptomatic; stenosis; vulnerable plaque; stroke